Notes for a Political Ecology of Dependency. The Case of Land Grabbing - Costantino, Agostina (Sociedad y Economía, 2013)
The importance of the land grabbing problem is not only related to the concentration ofnatural resources and exclusion of local communities, but also to the production of rawmaterials and food, which has strong environmental impacts (soil degradation, pollution,etc.). This paper focuses on the interpretive framework that would allow addressing theproblem of selective orientation of foreign land investment to some countries. We believethat the condition of dependency of these countries is crucial to understanding this phenomenon.Thus, we propose to analyze the land-grabbing problem in direct relation to thecondition of dependency of Latin American countries, and in this regard we suggest theneed for a theoretical framework denoted as the “Political Ecology of Dependency”.